Promoting public transport by improving its service quality - Noorazila, Asman (2014)
Population in Kampar town ,Perak, increased by 2013 and it will cause traffic congestion and pollution. To protect Kampar town, public transportation need improvement so that people in Kampar town like to use public transport. Quality of bus service decrease by 2011 until now. People refuse to riding bus and it will make the bus company cannot survive and people who cannot afford private transport will lost benefit to use public transport. This study purpose are to investigate service quality of public bus at Kampar town, to know which service quality have influence to customer satisfaction and to find gaps and proposed improvement of public bus at Kampar town. Survey have been administered at Kampar town and its surrounding area to collect data. The data have been analyzed using Microsoft excel to get the percentage of service quality, level of customer satisfaction and gaps of proposed improvement. From the result, customer satisfy with seat, safety from harassment, cleanliness of the bus, staff attitude, staff appearance, bus driving style, service hours of the bus, bus routes, number of bus transfer and walking distance from bus stop from home.customer not satisfy with seat availability, security of customer,s belonging, bus temperature, cleanliness of the station, punctuality of the bus, bus frequency, bus fare and information about bus schedule. Finally recommendation to improve quality service of public bus have been suggested which is higher the frequency of the service.The findings help to understand customer demand in Kampar town and provide information and suggestion so that the responsible parties can enhance the quality of public bus service and can attract customer to ride public bus.